Cross-Cultural Pedagogical Perspectives: A Collaborative Study with Indian Scholars in Childhood Education - Jamin, Nunung Suryana; Munirah, Munirah; Asfahani, Asfahani; Prusty, Anjana; Palayukan, Hersiyati (Absorbent Mind, 2024)
This collaborative study explores cross-cultural pedagogical perspectives in childhood education through partnerships with scholars from India. This research aims to explore how cultural factors influence teaching methodology, curriculum design, classroom management techniques, and assessment strategies in early childhood education settings. This research involved 15 informants, including education experts, educators, and practitioners from various cultural backgrounds in India, using qualitative research methods such as in-depth interviews, classroom observations, and document analysis. The results of this study underscore the importance of cultural sensitivity and inclusivity in designing effective pedagogical strategies, as well as the importance of collaborative efforts in fostering cross-cultural understanding and knowledge exchange. This study provides valuable insights and practical recommendations for educators, policymakers, and curriculum developers seeking to create culturally responsive and inclusive learning environments for young learner world.wide.